Przemiany systemowe i kulturowe implikowane wdrożeniem systemów zarządzania jakością : certyfikacja czy akredytacja systemów edukacyjnych? - Jasiczak, Jan; Korzeniowski, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The recertification process of quality management system ISO 9001:2000 in the Faculty of Commodity Science of Poznan University of Economics was carried out in May 2004. The five year period of system solutions running has been devoted not only to their maintenance, but first of all to their development and to understand that Total Quality Leadership seems to be the optimal direction of the TQM development. In this period special emphasis has been also placed on the implementation of Quality Management System confirmed with the requirements according to ISO 9001 and accreditation standards for educational systems. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 206-216